Static bending deflection and free vibration analysis of moderate thick symmetric laminated plates using multidimensional wave digital filters. (June 2018) - Tseng, Chien-Hsun
Highlights: A MDWDF is adopted for the bending deflection and free vibration of laminated plates. It offers high accuracy, stability and efficiency for a wide range of modulus ratios. Given a SCF, the network achieves more accurate prediction of the bending deflection. Assisted by the NLP, simulations indicate excellent performance as compared to HSDTs. Having the SCF for maximum bending deflection, the MDWDF outperforms HSDTs and LWPTs. Abstract: This paper aims to develop a multidimensional wave digital filtering network for predicting static and dynamic behaviors of composite laminate based on the FSDT. The resultant network is, thus, an integrated platform that can perform not only the free vibration but also the bending deflection of moderate thick symmetric laminated plates with low plate side-to-thickness ratios ( < = 20 ). Safeguarded by the Courant-Friedrichs-Levy stability condition with the least restriction in terms of optimization technique, the present method offers numerically high accuracy, stability and efficiency to proceed a wide range of modulus ratios for the FSDT laminated plates. Instead of using a constant shear correction factor (SCF) with a limited numerical accuracy for the bending deflection, an optimum SCF is particularly sought by looking for a minimum ratio of change in the transverse shear energy. This way, it can predict as good results in terms of accuracy for certain cases of bending deflection. Extensive simulation results carried out for the prediction of maximum bending deflection have demonstratively proven that the present method outperforms those based on the higher-order shear deformation and layerwise plate theories. To the best of our knowledge, this is the first work that shows an optimal selection of SCF can significantly increase the accuracy of FSDT-based laminates especially compared to the higher order theory disclaiming any correction. The highest accuracy of overall solution is compared to the 3D elasticity equilibrium one.